1977
DOI: 10.1037/0096-3445.106.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Semantic conditioning and generalization of the galvanic skin response-orienting reflex with overt and covert activity.

Abstract: The galvanic skin response was obtained from 36 college students in a differential semantic conditioning and generalization situation in which different groups were instructed to perform a pedal response whenever they heard a tone, covertly free associate whenever they heard a tone, or sit quietly and listen to words and tones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

1977
1977
1986
1986

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…First, there is the continued theoretical and experimental ambiguity associated with the concept of arousal (Lacey, 1967;Maitzman, 1975;Naatanen, 1973) and the absence of an acceptable measure of arousal in the present experiment. Second, results from other experiments have demonstrated the importance of significance as a predeterminer of the GSR index of the OR when differential contributions of arousal were clearly not involved (Maltzman et al, 1977;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is the continued theoretical and experimental ambiguity associated with the concept of arousal (Lacey, 1967;Maitzman, 1975;Naatanen, 1973) and the absence of an acceptable measure of arousal in the present experiment. Second, results from other experiments have demonstrated the importance of significance as a predeterminer of the GSR index of the OR when differential contributions of arousal were clearly not involved (Maltzman et al, 1977;.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulus significance is one of these complex determiners. It is particularly evident when established by instructions that impart signal value to stimuli, that is, instructions to perform an overt (Luria & Vinogradova, 1959;Maltzman & Raskin, 1965 or covert act on signal (Maltzman, Gould, Pendery, & Wolff, 1977;Maltzman & Raskin, 1965. Aside from occasional failures (e.g., Barry, 1977;Becker & Shapiro, 1980), which may be due to complexity of instructions and to difficulty in specifying the essential variables contained in instructions, as well as a variety of other methodological problems, the great majority of experiments report that signal value does enhance the psychophysiological changes reflecting an OR (e.g., Latash, 1968;Luria, 1973;Luria & Homskaya, 1970;Luria & Vinogradova, 1959;Maltzman, Gould, Barnett, Raskin, & Wolff, 1979;Sokolov, 1963).…”
mentioning
confidence: 99%
“…In a review of the Soviet classical conditioning literature, Razran (1957) reported that UR magnitude is used as a measure of US effectiveness. In this country, it has been found that UR magnitude is also predictive of CR efficacy (Maltzman et al, 1977). Therefore, it may be concluded that UR magnitude can be used as a way of assessing whether or not a light stimulus functions as an effective US in producing conditioned alpha blocking or generating CRs for other classically conditioned response systems.…”
Section: Discussionmentioning
confidence: 99%
“…Harvey and Wickens (1971) reported that, for the GSR response system, instructions influenced CR efficacy through UR magnitude. Maltzman and his associates (Maltzman et al, 1977) also found that it was possible to use UR magnitude as a way to predict the occurrence of CRs in a semantic conditioning study of the GSR response system. These investigators found better semantic conditioning for the subjects who demonstrated effective UR magnitudes prior to the start of the conditioning study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation